PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PERANGKAT PENDUKUNG TERHADAP PENYUSUNAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada Badan Pengelola Keuangan dan Aset Daerah Kota Kendari) - Aswati, Wa Ode; Bustam, Muthmaina Auliah (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTThe research aim to know effect of human resources quality and supporting device to formation financial statement of local government (Study on Badan Pengelola Keuangan dan Aset Daerah Kendari)The hypothesis of this research is human resources quality and supporting device have a significant effect to formation financial of local government. The number of sample that be used for this analysis is 26 respondent in financial statement of local government team. Technique withdrawal of sample with purposive sampling method. To answer the hypothesis is used analysis linear regression multiply combine with SPSS 29. T-test showed that human resources quality have t counted 2,526 larger than t-table 1.713 and supporting device have t count 5,727 larger than t table. This matter indicated all of independent variable have effect significantly to formation financial statement of local government. Coeffisient adjusted R Square result of regression equal to 0,720. This matter indicated variable variation that is human resources quality and supporting device can explain 72% of dependent variable. While 28% explained by other independent variable which do not research.The results of this study indicated that the human resources quality has significant effect on the formation financial statement of local government, so does supporting device has significant effect on the formation financial statement of local government. Key words : Human Resources Quality, Supporting Device and Formation Financial Statement of Local Government.